The Tree of Knowledge Paradigm for Integrating Islam and Science: A Historical Study of Islamic Higher Education - Mokodompit, Adesisilia; Mas'ud, Ali; Abu Bakar, M.Yunus (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The dichotomy between religious sciences and secular sciences remains a fundamental challenge in the development of Islamic higher education in Indonesia. This separation has resulted not only in fragmented knowledge structures but also in the weakening of holistic academic and moral formation. In response to this issue, the Tree of Knowledge paradigm developed at UIN Maulana Malik Ibrahim Malang represents a systematic effort to integrate Islam and modern science within a unified, tauhid-based epistemological framework. This study aims to examine the historical background, epistemological foundations, practical implementation, and contemporary relevance of the Tree of Knowledge paradigm in shaping Islamic higher education in the global and digital era. This research employs a qualitative approach using a library research Design. Data were collected through critical analysis of scholarly books, peer-reviewed journal articles, and institutional documents related to Islamic epistemology, knowledge integration, and the Tree of Knowledge model. Data analysis used content analysis and historical analysis to explore the epistemological structure, implementation dynamics, and challenges of integrative knowledge paradigms in Islamic universities. The findings reveal that the Tree of Knowledge paradigm functions not merely as a symbolic representation but as an operational framework guiding curriculum development, interdisciplinary research, and integrative academic culture. The paradigm successfully positions revelation, reason, and empirical experience in a synergistic relationship. The study implies that the Tree of Knowledge offers a strategic foundation for developing Islamic higher education institutions that are spiritually grounded, intellectually competitive, and capable of contributing ethically and constructively to global civilization in the digital age.